Progress report on the Project on Integration and Harmonization of Instruments for Social Statistics (INAES) (ECLAC [Santiago]CL, 2008)
Provides a general description of the activities conducted to date in each of the phases of execution of the project and the methodology applied, as well as the results obtained and the outcomes.
Keywords: STATISTICAL SERVICES